Design of student chair using local wood with ergonomic approach and finite element-based structural validation - Taufik Ramadhan Fitrianto; Bahtiar Rahmat; Siska Anggiriani; Desy Mulyosari; Nurhanifah Nurhanifah; Alfani Risman Nugroho; Muhammad Afif Affandi (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
This study presents the design and structural validation of an ergonomic student chair using locally sourced Indonesian wood species. The research integrates anthropometric analysis, computer-aided design, and Finite Element Method (FEM) simulations to ensure both comfort and mechanical reliability. Anthropometric data from Indonesian students determined key seating dimensions, while FEM analysis evaluated structural performance under static loading conditions. Four wood species—teak (Tectona grandis), mahogany (Swietenia macrophylla), pine (Pinus merkusii), and sonokeling (Dalbergia latifolia)—were compared based on stress distribution, total deformation, and factor of safety (FoS). All materials satisfied the minimum safety factor of 1.5, confirming adequate strength for classroom use. Sonokeling achieved the highest FoS (2.47), while pine offered the best efficiency index (22.6) when performance was normalized by cost. The results demonstrate that locally available wood can provide safe, ergonomic, and economically feasible alternatives to imported materials. This integrated ergonomic–engineering approach supports sustainable, affordable, and human-centered furniture design for educational environments.